1998
DOI: 10.1007/s004410051197
|View full text |Cite
|
Sign up to set email alerts
|

An immunohistochemical and in situ hybridisation study of the postnatal development of uncoupling protein-1 and uncoupling protein-1 mRNA in lamb perirenal adipose tissue

Abstract: In the lamb, the uncoupling protein-1 (UCP1) content of perirenal adipose tissue at birth is an important factor in heat production by non-shivering thermogenesis and the prevention of hypothermia. This study examines UCP1 gene expression and protein content in perirenal adipose tissue over the first 15 days of life by in situ hybridisation and immunohistochemistry. UCP1 mRNA was detected at birth in 30% of adipocytes, and in approximately 24% of fat cells at 2 days of life. However, by 5 days of age and there… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
13
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 22 publications
2
13
0
Order By: Relevance
“…At a molecular level, this change can be followed by the increased expression during fetal life of the BAT marker gene uncoupling protein 1 (UCP1), which confers the thermogenic function of this tissue (7). Our studies in the ovine have demonstrated that expression of UCP1 in perirenal adipose tissue (PAT) is totally suppressed within 5 d after birth despite being born into an environmental temperature below the thermoneutral zone (8). Attempts to reinduce UCP1 expression in the ovine by administration of a ␤ 3 -adrenoreceptor agonist during the first month of life have been met with limited success (9,10), agreeing with the morphological and thermogenic activity evidence that ovine BAT is irreversibly transformed to WAT during the first weeks of life (2,11).…”
mentioning
confidence: 88%
“…At a molecular level, this change can be followed by the increased expression during fetal life of the BAT marker gene uncoupling protein 1 (UCP1), which confers the thermogenic function of this tissue (7). Our studies in the ovine have demonstrated that expression of UCP1 in perirenal adipose tissue (PAT) is totally suppressed within 5 d after birth despite being born into an environmental temperature below the thermoneutral zone (8). Attempts to reinduce UCP1 expression in the ovine by administration of a ␤ 3 -adrenoreceptor agonist during the first month of life have been met with limited success (9,10), agreeing with the morphological and thermogenic activity evidence that ovine BAT is irreversibly transformed to WAT during the first weeks of life (2,11).…”
mentioning
confidence: 88%
“…BAT is detected in newborns but its thermogenic activity decreases rapidly after birth (21). In young humans, BAT seems to be converted into white adipose tissue as has been described for ruminants (22,23). However, it is possible to detect BAT in certain conditions: in outdoor workers exposed to cold conditions (24) or in several pathological situations such as pheochromocytoma or hibernoma (21,25,26).…”
mentioning
confidence: 99%
“…Uncoupling protein (UCP)1, a 32-kDa protein in the inner mitochondrial membrane and exclusively found in BAT, appears in the fetus around midgestation (4), and thereafter its expression in perirenal adipose tissue increases up to term before rapidly declining so that it is undetectable by the end of the first month after birth (5). Gene expression of UCP1 is nutritionally regulated, at least in part, and is downregulated in response to late-gestation maternal nutrient restriction (6).…”
mentioning
confidence: 99%